(3GdeQGLYI GdOhdjI hYhdeI CShGb QCS GdeGds - (3Cejf GdSjO CMeO(B, (3dWajs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2005)
(3GdYhdeI hGdJLGQI GdOhdjI hCKQgG Ydi GdeMGSHI hGdeQGLYI(B- (3GdeQGLYI GdNGQLjI aj Xd GdHjFI GdOhdjI(B- (3GdJhGab GdOhdj ddeQGLYI(B- (3eJWdHGJ GdJYdje hGdNHQI hGdJCgjd ddeQGLYjf Ydi GdeSJhi GdOhdj(B- (3CNdGbjGJ hBOGH GdegfI Ydi GdeSJhi GdOhdj(B- (3JbGQjQ GdeQGLYI GdOhdjI(B- (3GdeQGLYI GdOGNdjI Ydi GdTQcGJ GdOhdjI(B- (3GdeQGLYI GdOhdjI hMhceI EOGQI GdTQcGJ(B- (3GdJLGQI GdEdcJQhfjI hCKQgG Ydi NOeGJ GdJCcjOs
Keywords: (3GdJLGQI GdOhdjIs; (3GdYhdeI(B- (3GdLhGfH GdGbJUGOjIs; (3GdeQGLYI GdOhdjIs; (3QCS GdeGd(B- (3GdLhGfH GdGbJUGOjIs; (3eQGLYI GdMSGHGJs